Peningkatan Pola Hidup Bersih dan Sehat (PHBS) di RW 3 Kelurahan Madyopuro Kecamatan Kedungkandang Kota Malang - Andia Kusuma Damayanti; Lies Purnamasari; Azis Abdullah (Jurnal ABM Mengabdi, 2017)
RW 3 community Madyopuro Village District of Kedungkandang totaled 18 918 people, made up of 7 RT with 524 heads of household and 81 houses declared still unhealthy. This area is still relatively poor with income families are still minimal. Habits are currently common as taking out the trash arbitrarily, bathing and washing clothes in the river, some people do not have toilets, so must the river , wash your hands in the river and do not use soap, still a lot of people smoking in the house, ventilation no / do not meet the standards of home healthy with free incoming air circulation so that the humidity can be maintained, the tiles are still on the ground , the lack of adequate lighting, home some still klenengan (½ walls, roofs of zinc). Efek happens some people often experience physical disorders such as: pressure high blood pressure, lung, ached, DB, infectious disease. To create a society that is healthy, they invited committed to healthy living through a clean and healthy lifestyle. Through the training program using LEARNING system of, by and with the community in accordance with the local culture and supported by sound public policy that health can also be done while the behavior modification techniques for ventilation and light can be overcome with minimum standards improvement program that is making a healthy home ventilation and lighting the way: the creation of a natural ventilation by means of which the sun.